2013
DOI: 10.3109/00365521.2012.752030
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma as extracolonic manifestation of Lynch syndrome indicatesSEC63as potential target gene in hepatocarcinogenesis

Abstract: For the first time, an HCC with characteristic molecular features of association with Lynch syndrome is described. The pro-carcinogenic growth behavior of hepatocytes with low SEC63 expression in the murine model indicates a potential role for SEC63 in hepatocarcinogenesis in general, but this needs further functional validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…DNA MMR genes play an important role in maintaining the integrity and stability of the genetic information and avoiding the occurrence of genetic mutations, which is a function closely related to the development of tumors [15,16]. It has been reported that MMR defects can lead to the development of colon, pancreatic, stomach, esophageal, ovarian and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DNA MMR genes play an important role in maintaining the integrity and stability of the genetic information and avoiding the occurrence of genetic mutations, which is a function closely related to the development of tumors [15,16]. It has been reported that MMR defects can lead to the development of colon, pancreatic, stomach, esophageal, ovarian and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For SEC63 , frameshift mutations caused by microsatellite instability were found in 37.5% of microsatellite-unstable gastric cancers, 82 48.8% of colorectal cancers, 82 56% of small-bowel cancer associated with hereditary non-polyposis colorectal cancer 83 and in one case of hepatocellular carcinoma associated with Lynch syndrome. 84 However, functional analyses to further uncover the role of Sec63 in human carcinogenesis were solely conducted by Casper et al , 84 who showed that a low hepatic expression of SEC63 correlated with a decreased apoptosis rate and an increased proliferative activity of hepatocytes in BXD mice. Altogether, these studies indicate a potential role of SEC63 as a tumor suppressor gene in the carcinogenesis of gastric cancer, colorectal cancer and hepatocellular cancer (HCC) without, however, providing a link of disrupted Sec63 function to tumor cell biology in these entities.…”
Section: Mutation and Overexpression Of Sec Genes mentioning
confidence: 99%
“…These downstream targets of XBP1s transcription factor were not selected randomly; they have certain roles in the events pertaining to cellular differentiation. High SEC63 expression has been shown to have an involvement in apoptosis and reduced proliferation in hepatic tumors ; ERDJ4 has been shown to have a crucial role in B cell differentiation in the event of hematopoiesis . Besides, DNAJC3 levels are known to increase during plasma cells differentiation ; the expression of PDIA3 and DNAJC3 was shown to be upregulated during T‐helper cell differentiation and treatment with IRE1α's endoribonuclease activity specific inhibitor 4μ8c downregulated their expression via inhibiting XBP1 mRNA splicing .…”
Section: Resultsmentioning
confidence: 99%